POSITIONING PELUM AS MESRAN BERDASARKAN PERSEPSI KONSUMEN - Rizal Edy Halim; Ahamad Daromi (Universitas Trisakti, 2007)
Perception has an important role in determining consumer decision making. What consumers want to buy is often infucenced by the perception that he or she has about a particular product brand. So does in the lubricant industries, especially four-engine motorcycle lubricant. In this industry, where the competition is very high, each company must use their strategy effectively. One of those strategies is positioning- the act designing of the company offering and image to occupy a distinctive place in the mind of the target market (Kotler, 2000). The main purpose of this study is to identify the positioning of Mesran among its five competitors (Top One, Castrol, Shell, Pennzoil, and Agip) based on consumer perception, specifically a student of University of Indonesia. There are also three major purposes of this study: First, to identify the behavior of four-engine motorcycle lubricant consumers. Second, to identify the crucial attribute of four-engine motorcycle lubricant. Third, to identify the positioning of Mesran based on consumer perception. The tools of the analysis of this study are the Attribute Rating (AR) Perceptual Map that can give us a picture of consumer perception about product attributes. These studies also use analysis tools such as Factor analysis and analysis of mean score